Analysis of factors affecting the surgical efficacy for elderly intertrochanteric fracture - Yu, Xiang; Li, Yu-Zhi; Lu, Hai-Jian; Ao, Rong-Guang; Liu, Bing-Li (Frontiers in Surgery, 2025)
ObjectiveTo explore the relevant factors affecting the efficacy of surgery for intertrochanteric fracture.MethodsA retrospective case series study was conducted to analyze the clinical data of 212 patients with intertrochanteric fractures from January 2021 to December 2023. The patients, comprising 100 males and 112 females aged 65–98 years old (mean age 77.8 ± 10.5 years), were categorized based on fracture healing outcomes into a normal healing group (163 cases) and an abnormal healing group (49 cases, including 2 cases of non-union). Factors such as gender, age, injury side, fracture classification, thickness of femoral lateral wall, medial support, tip-apex distance and fixation position were recorded and analyzed through Logistic regression to identify the main factors influencing fracture healing.ResultsUnivariate analysis revealed statistically significant differences in AO classification, Evans-Jensen classification, medial support, tip-apex distance and main screw position between the two groups (P < 0.05). Logistic regression analysis indicated that AO type A1 (OR = 1.030), medial support (OR = 0.395), tip-apex distance ≤25 mm (OR = 0.266) and main screw located in the middle and lower part of the femoral head (OR = 0.986) were significantly related to fracture union (P < 0.05). The Oxford score of the normal fracture healing group (mean 42.6 ± 4.5 points) was higher than that of the abnormal healing group (mean 35.4 ± 3.2 points) (P < 0.05).ConclusionsThe stability of internal fixation is the most important factor affecting intertrochanteric fracture healing. The medial support, tip-apex distance ≤25 mm and the position of the screw are helpful for fracture healing and recovery of joint function.